EFEKTIVITAS PENERAPAN METODE PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISIONS DAN TEAM ASSISTED INDIVIDUALIZATION PADA MATERI REGRESI LINIER - Andhita Dessy Wulansari (Cendekia: Kependidikan dan Kemasyarakatan, 2014)
Abstract; in general, learning statistics in class do not working at all, active lecturer predominate and student tend to passive as good hearer. Conventional study like this, make student only memorizing and working procedure without comprehend concept in fact. According to Hudojo, "With cooperative learn method give a chance to its student to develop themselves". Of course not all of cooperative learn method can be applied, should be selected as same as the field condition. This research, cooperative learn method of TAI (Team Assisted Individualization) and STAD (Student Teams Achievement Divisions) selected to be applied. Aim of this research is to compare applying effectiveness empirically of cooperative learn method between TAI, STAD and conventional through result statistics 2 of regression linear, grade 5th student of STAIN Ponorogo year of academic 2013 / 2014. According to data analysis using of One Way ANOVA statistics method, concluded that, there is difference result, learn statistics 2 of regression linear between class using learning method TAI, STAD and conventional. Where learning method TAI more effective than STAD and conventional; and STAD more effective if compared to conventional learning method.ملخص: كان تدريس مادة الاحصائيات –عامة- لا يسير سيرا متوازنا، لأن المدرس هو المهيمن والفاعل والطلاب صامتون. أدى هذا النوع من التدريس إلى أن يحفظ الطلاب ويعملون رسميا ولا يفهمون حقيقة النظريات. يري هودوجو أن تطبيق طريقة التعليم الاشتراكي يعطى الطلاب الفرصة الواسعة للتنمية الذاتية. وطبعا أن جميع أنواع التعلم الأشتراكي لا يمكن تطبيقها، بل لابد من اختيار الأنسب منها بالواقع. يختار هذا البحث تطبيق التعليم الاشتراكي نوع TAI (Team Assited Individualization)  و STAD (Student Team Achievement Division)   . وأهداف هذا البحث هي المقارنة واقعيا بين تطبيق التعليم الاشتراكي نوع TAI AND STAD  والتقليدي، عبر نتائج تعلم الاحصائيات (2) مادة REGRESI LINIER  لدى طلاب الجامعة الإسلامية الحكومية فونوروغو المستوى الخامس العام الدراسى 2013/2014 . اعتمادا على تحليل البيانات باستخدام طريقة احصائية One Way ANOVA  يستنتج منها نتائج أن هناك فرق في نتائج تعلم مادة الاحصائيات (2) في مادة regresi linier بين الصف المستخدم طريقة التعليم TAI, STAD  والطريقة التقليدية. وتكون طريقة TAI أكثر فعالا بالنسبة إلى طريقة STAD  والطريقة التقليدية ، وطريقة STAD  أكثر فعالا بالنسبة إلى الطريقة التقليدية.Keywords: Efektivitas, TAI, STAD, Statistika